Chronologic changes in serum hepatitis B virus DNA, genotypes, surface antigen mutants and reverse transcriptase mutants during 25‐year nationwide immunization in Taiwan - Hsu, H.‐Y.; Chang, M.‐H.; Ni, Y.‐H.; Chiang, C.‐L.; Wu, J.‐F.; Chen, H.‐L.; Chen, P.‐J.; Chen, D.‐S. (Journal of viral hepatitis, 2017)
Summary We investigated breakthrough infection and hepatitis B virus (HBV) genetic changes in immunized subjects after 25 years of a universal infant immunization. Specifically, serum HBV DNA, genotypes, surface antigen mutants and nucleoside analog‐resistant (NAr) mutants were assessed in 2853 subjects (<25 years old) surveyed in 2009, and these data were compared with the data from previous serosurveys. A comparison across different age‐stratified groups using the 2009 data revealed a significant increase in the seropositive rate of anti‐HBc (5.51% vs 12.38%, P=.001) and HBV DNA (1.13% vs 3.96%, P=.007) between those 17‐22 and 23‐24 years of age, possibly due to selective infant immunization in 1984‐1986. Well‐characterized NAr mutants, potential NAr mutants and surface “a” determinant mutants were detected in none, 15 (45.5%) and nine (27.3%) of 33 HBV DNA‐positive subjects, respectively. Of 15 immunized, HBV DNA‐positive young adults (18‐24 years), three (20%) carried “a” determinant mutants. Amongst 1176 HBsAg‐negative subjects evaluated for occult HBV infection, those seropositive for anti‐HBc had a higher seropositive rate for HBV DNA (10/110, 9.1% vs 7/1066, 0.66%; P<.001) and “a” determinant mutants (4/110, 3.6% vs 0/1066; P<.001) than those seronegative for anti‐HBc. Overall, the HBsAg‐positive subjects in six serosurveys showed no significant increase in genotype C frequency in the comparison between the vaccinated and unvaccinated cohorts (25/98, 25.5% versus 14/79, 17.7%, P=.188). Over the 25‐year programme, there was no increase in the prevalence of genotype C in HBsAg carriers and no increase in breakthrough HBV infection or surface mutant prevalence beyond adolescence. Nucleic acid amplification should still be considered the primary screening method for occult hepatitis B detection in high‐risk recipients.